Fools and Wise Men - Bercuson, David Jay (McGraw-Hill Ryerson, 1978)
This is the story of the One Big Union--the people who built and those who tore it down. The tale is well known in its broad outlines to many people with an interest in Canadian history, but because it was a failure--and history is generally about winners--few have a clear idea of what the OBU was, why it was created and the reasons for its rapid demise. I have long believed the story should be told in full, because it carries with it an explanation of what happened to the spirit of radicalism and revolt that motivated many working people in the west prior to 1920. Sometimes the explanation of a failure is more revealing than the description of a success. --Author's preface
Keywords: Canada; One Big Union; Trade unions